Assessment of a strategy combining ambulatory blood pressure, adherence monitoring and a standardised triple therapy in resistant hypertension. (2nd November 2021) - Polychronopoulou, Erietta; Burnier, Michel; Ehret, Georg; Schoenenberger-Berzins, Renate; Berney, Maxime; Ponte, Belen; Erne, Paul; Bochud, Murielle; Pechère-Bertschi, Antoinette; Wuerzner, Gregoire
Abstract: Purpose: Poor adherence to drug therapy and inadequate drug regimens are two frequent factors responsible for the poor blood pressure (BP) control observed in patients with apparent resistant hypertension. We evaluated the efficacy of an antihypertensive management strategy combining a standardised therapy with three long acting drugs and electronic monitoring of drug adherence in patients with apparent resistant hypertension. Materials and Methods: In this multicentric observational study, adult patients with residual hypertension on 24 h ambulatory BP monitoring (ABMP) despite the use of three or more antihypertensive drugs could be included. Olmesartan/amlodipine (40/10 mg, single pill fixed-dose combination) and chlorthalidone (25 mg) were prescribed for 3 months in two separated electronic pills boxes (EPB). The primary outcome was 24 h ambulatory systolic BP (SBP) control at 3 months, defined as mean SBP <130 mmHg. Results: We enrolled 48 patients (36.0% women) of whom 35 had complete EPB data. After 3 months, 52.1% of patients had 24 h SBP <130 mmHg. 24 h SBP decreased by respectively −9.1 ± 15.5 mmHg, −22.8 ± 30.6 mmHg and −27.7 ± 16.6 mmHg from the tertile with the lowest adherence to the tertile with the highest adherence to the single pill combination ( p = 0.024). A similar trend was observed with tertiles of adherence to chlorthalidone. Adherence superior to 90% was associated with 24 h systolic and diastolic blood pressure control in multiple logistic regression analysis (odds ratio = 14.1 (95% confidence interval 1.1–173.3, p = 0.039). Conclusions: A simplified standardised antihypertensive therapy combined with electronic monitoring of adherence normalises SBP in about half of patients with apparent resistant hypertension. Such combined management strategy enables identifying patients who need complementary investigations and those who rather need a long-term support of their adherence.